Groundwater Potential for Water Utilization in Sai Village - Junna, Isra; Najimudin, Didin (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2024)
Sai Village is one of the villages that is included in the administrative area of Soromandi District, Bima Regency, West Nusa Tenggara. The hilly topography of the village and the sea coast of the Flores Strait makes it very difficult for Sai Village to meet the water needs of agricultural irrigation, the conditions of the hills are arid so that farmers in Sai Village only rely on rainwater for cultivation or rain-fed land types. Sai Village relies on agricultural products for survival as evidenced by data on the number of farmers of 900 people and 311 farm laborers out of a total population of 3,079 people. Limited air irrigation is a major problem in agriculture in Sai Village, especially during the dry season. To overcome this problem, it can only be overcome by drilling water wells in areas that are considered to have the potential to contain fresh water with a total data of 69.29%. The water pump method is very effective in providing good water to rice, onions and crops, in the Sai 1 land area with an area of 35 hectares with a water requirement of 0.108 liters/second and the location of Sai 2 land with an area of 93 hectares with a water requirement of 0.245 liters/second whole water. Using a pump that circulates air of 0.0567 m3/second with a performance of 190.08 m3/day with a total engine operating hours of 23 hours 45 minutes.